Role of CT density in PET/CT-based assessment of lymphoma - Flechsig, Paul; Walker, Christina; Kratochwil, Clemens; König, Laila; Holland-Letz, Tim; Kauczor, Hans-Ulrich; Haberkorn, Uwe; Giesel, Frederik L. (Molecular imaging & biology, 2018)
PurposeIn patients with Hodgkin (HL) and non-Hodgkin lymphoma (NHL), primary staging, as well as intermediate and late response assessment, is often performed by integrated 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) positron emission tomography/X-ray computed tomography (PET/CT). The purpose of this analysis was to evaluate if findings in patients with histopathologically proven HL or NHL might correlate with semi-automated density measurements of target lesions (TLs) in the CT component of the integrated PET/CT examination.ProceduresAfter approval by the institutional review board, 176 lymph nodes (LN) in 90 PET/CT examinations of 90 patients were retrospectively analyzed (HL, 108 TLs out of 55 patients; NHL, 68 TLs out of 35 patients). PET/CT was performed for reasons of primary staging, response evaluation as interim PET, or as final examination after therapy, according to the clinical schedule. Analyses of TLs were performed on the basis of tracer uptake (SUV) 60 min after tracer injection and volumetric CT histogram analysis in non-contrast-enhanced CT.ResultsAll patients were diagnosed with HL or NHL in a pretreatment biopsy. Prior to therapy induction, staging of all patients was performed using contrast-enhanced CT of the neck to the pelvis, or by [18F]FDG PET/CT. Of the 176 TLs, 119 were classified as malignant, and 57 were benign. Malignant TLs had significantly higher CT density values compared to benign (p < 0.01).ConclusionDensity measurements of TLs in patients with HL and NHL correlate with the dignity of TLs and might therefore serve as a complementary surrogate parameter for the differentiation between malignant and benign TLs. A possible density threshold in clinical routine might be a 20-Hounsfield units (HU) cutoff value to rule out benignancy in TLs that are above the 20-HU threshold.